2022
DOI: 10.3389/fpubh.2022.996179
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal adverse events associated with semaglutide: A pharmacovigilance study based on FDA adverse event reporting system

Abstract: BackgroundSemaglutide was approved for treatment of type 2 diabetes mellitus (T2DM) and chronic weight management in obesity or overweight adults. However, real-world data regarding its long-term gastrointestinal safety and tolerability in large sample population are incomplete. We evaluated semaglutide-associated gastrointestinal safety signals by data mining of the FDA pharmacovigilance database.MethodsReporting odds ratio (ROR) was employed to quantify the signals of semaglutide-related gastrointestinal adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 45 publications
0
22
0
2
Order By: Relevance
“…For retinopathy, this has been shown in PIONNER for semaglutide [ 31 ], and for pancreatitis, in PIONNER for semaglutide, in AWARD for dulaglutide, and in LEADER for liraglutide [ 31 , 72 , 73 ]. Gastrointestinal AEs, such as nausea, diarrhea, and vomiting, are higher in some studies [ 62 ], while in PIONNER for semaglutide, they have a similar incidence with placebo groups, or are majority mild forms, as in STEP for semaglutide [ 31 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…For retinopathy, this has been shown in PIONNER for semaglutide [ 31 ], and for pancreatitis, in PIONNER for semaglutide, in AWARD for dulaglutide, and in LEADER for liraglutide [ 31 , 72 , 73 ]. Gastrointestinal AEs, such as nausea, diarrhea, and vomiting, are higher in some studies [ 62 ], while in PIONNER for semaglutide, they have a similar incidence with placebo groups, or are majority mild forms, as in STEP for semaglutide [ 31 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 The most frequent adverse events in the present study were gastrointestinal, such as nausea (reported by 30% of patients). Gastrointestinal side-effects were expected, due to the results of previous studies, [15][16][17] and patients were warned of the possibility of their appearance. Importantly, these side-effects did not cause discontinuation of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Last, a recent pharmacovigilance study based on the Food and Drug Administration (FDA) adverse event reporting system (FAERS) reports 10 cases of serious (0.56%) and 2 cases of nonserious appendicitis (0.05%) associated with semaglutide over the span of 2018 to 2022. 14 One mentionable limitation of the literature is that there are little to no details on the acuity and outcomes of appendicitis, nor specific mentioning on timing and dosage relative to the adverse event to better gauge a correlation. The treatment method, including whether or not an appendectomy was performed, and type of surgery remain unknown in the bulk of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Last, a recent pharmacovigilance study based on the Food and Drug Administration (FDA) adverse event reporting system (FAERS) reports 10 cases of serious (0.56%) and 2 cases of nonserious appendicitis (0.05%) associated with semaglutide over the span of 2018 to 2022. 14…”
Section: Discussionmentioning
confidence: 99%